Implementasi Metode Eklektik dalam Pembelajaran Mahāratul Kalām untuk Santri Pemula - Samin, Samin; Mulhendra, Mulhendra; Febriansyah, Hari (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
This study aims to explore the application of eclectic methods in teaching mahāratul kalām among novice students in a pesantren. The eclectic method, which combines various teaching approaches, is expected to improve Mahāratul kalām  Santri in a more interactive and engaging way. We collected data through in-depth interviews, classroom observations, and documentation using a qualitative approach and case study design. The results of the study showed that the application of the eclectic method significantly increased the mahāratul Kalām of students, as well as increased their motivation and confidence in communicating using Arabic. Students feel more involved in the learning process when various techniques are used, such as role-playing and group discussions. Despite the challenges in preparing suitable teaching materials and time constraints, the success achieved shows that eclectic methods can be an effective solution in teaching Arabic. This study recommends the further development of eclectic methods in Arabic language teaching and offers suggestions for further research with a quantitative approach to measure impact more objectively.